2011
DOI: 10.1002/pssc.201084186
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic behavior in Mn‐doped LaAlO3 single crystals

Abstract: LaAlO3 single crystals were doped with transition element Mn by thermal diffusion method for investigation of ferromagnetism. With increasing the annealing temperature TN, ferromagnetism begins to appear when TN equals 750 °C, which is indicated by small magnetic hystersis (M ‐H) loop with low coercive field of 60 Oe measured at 60 K. After TN arrives at 1300 °C, obvious M ‐H loop can be observed at 60 K and the M ‐T curve displays sharp Curie phase transition, which shows an unambiguous ferromagnetism. A boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…However, there are few studies related to half‐metallic ferromagnetic (HMF) and optical properties of LAO after doping with TM. [ 24–26 ] Zylberberg and Zuo‐Guang modulated the characteristics of LAO by doping of bismuth at La site and concluded the increased dielectric properties after doping. [ 27 ] Furthermore, Sandeep et al [ 28 ] theoretically studied the effect of concentration‐dependent Nd substitution on structural stability, magnetic, and electronic features of cubic phase of lanthanum aluminate using mBJ + U approximation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are few studies related to half‐metallic ferromagnetic (HMF) and optical properties of LAO after doping with TM. [ 24–26 ] Zylberberg and Zuo‐Guang modulated the characteristics of LAO by doping of bismuth at La site and concluded the increased dielectric properties after doping. [ 27 ] Furthermore, Sandeep et al [ 28 ] theoretically studied the effect of concentration‐dependent Nd substitution on structural stability, magnetic, and electronic features of cubic phase of lanthanum aluminate using mBJ + U approximation.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are few studies related to half-metallic ferromagnetic (HMF) and optical properties of LAO after doping with TM. [24][25][26] Zylberberg and Zuo-Guang modulated the characteristics of LAO by doping of bismuth at La site and concluded the increased dielectric properties after doping. [27] Furthermore, DOI: 10.1002/pssb.202300206…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, diluted magnetic semiconductors have obtained much consideration due to their applications in spintronics devices [8,9]. Moreover, induction of ferromagnetism in nonmagnetic Perovskites compound is significant from experimentally and theoretically prospective because of spin functionality addition to host crystal [10][11][12][13]. In addition to this, multiferroic compounds are being obtained by doping of transition metal (TM) [14].…”
Section: Introductionmentioning
confidence: 99%
“…[13] Limited studies have been observed to date on the ferromagnetic and optical properties of the transition metal-doped LaAlO 3 . [16][17][18] Hong-Sheng et al studied the modification of the band gap in β -SiC and reported the change from an indirect to a direct band gap and the decrease of the energy band gap with doping the N-atom for the C atom. [19] Fang et al have satisfactorily explained the manifestation of an additional absorption peak in the experiments through the doping studies of KMgF 3 .…”
Section: Introductionmentioning
confidence: 99%